Metodologie i mody metodologiczne we współczesnej humanistyce (literaturoznawczej) - Stanisław Balbus (Przestrzenie Teorii)
Methodology is a "visiting-card" of nomothematicity within every science, and even if a given discipline as a whole is not considered a nomothematic one. However, behind every methodology stands a definite epistemology thanks to which a revelation of the subject of considerations and at the same time of the studying object. Thus, methodology is an epistemological necessity and only in this sense may aspire to scientific aesthetics which - as proved by P. Dirac - is identical with real science.